2006
DOI: 10.1158/1078-0432.ccr-06-0688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raloxifene on the Incidence of Invasive Breast Cancer in Postmenopausal Women with Osteoporosis Categorized by Breast Cancer Risk

Abstract: Purpose: To assess the effect of raloxifene, indicated for osteoporosis treatment and prevention, on invasive breast cancer in subgroups of postmenopausal women defined by risk factors for breast cancer. Experimental Design: Data from the 4-year Multiple Outcomes of Raloxifene Evaluation (MORE) trial (N = 7,705) and a follow-up study, the 4-year Continuing Outcomes Relevant to Evista (CORE) trial (N = 4,011), were analyzed. Prespecified subgroups were defined by age (z65 versus <65 years), age at menopause (z4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 22 publications
(21 reference statements)
0
32
0
1
Order By: Relevance
“…However, the effect was greater in women with increased risk of developing breast cancer, varying from 33% to 89% decreases in breast cancer occurrence congruent with the estimated risk. 12 This proved that the effect of raloxifene was greater in higher-risk women. Other examinations of the MORE study data have shown that the reduction of breast cancer risk seen in the use of raloxifene is dependent on the level of endogenous estrogen ( Fig.…”
Section: Raloxifene Chemoprevention Studiesmentioning
confidence: 87%
“…However, the effect was greater in women with increased risk of developing breast cancer, varying from 33% to 89% decreases in breast cancer occurrence congruent with the estimated risk. 12 This proved that the effect of raloxifene was greater in higher-risk women. Other examinations of the MORE study data have shown that the reduction of breast cancer risk seen in the use of raloxifene is dependent on the level of endogenous estrogen ( Fig.…”
Section: Raloxifene Chemoprevention Studiesmentioning
confidence: 87%
“…Raloxifene increased the risk of venous thromboembolic disease (RR 3.1, 95 % CI 1.5-6.2) but not the risk of endometrial cancer (RR 9.8, 95 % CI 0.2-2.7). Lippman et al [67] analysed data from the 4-year MORE trial and a follow-up study, the 4-year Continuing Outcomes Relevant to Evista (CORE) trial. Use of raloxifene was associated with a reduced breast cancer risk in both women at lower and those at higher breast cancer risk but the effect of raloxifene was greater in women with a family history of breast cancer.…”
Section: Treatment With Raloxifenementioning
confidence: 99%
“…The Continuing Outcomes Relevant to Evista (CORE) trial was conducted to examine the effect of 4 additional years of raloxifene therapy on the incidence of invasive breast cancer in women in MORE who agreed to continue in CORE [11][12]. There were 3510 women who had been randomly assigned to receive raloxifene (either 60 or 120 mg/day) in MORE who were assigned to receive raloxifene 60 mg/day in CORE.…”
Section: Continuing Outcomes Relevant To Evista ® (Core) Trialmentioning
confidence: 99%
“…During the 4 years of the CORE trial, there were 61 cases of breast cancer (30 in the placebo group and 31 in the raloxifene group) that were confirmed by adjudication [11][12]. Of the 61 breast cancer cases, 52 cases (28 in the placebo group and 24 in the raloxifene group) were classified as invasive breast cancer.…”
Section: Core Trialmentioning
confidence: 99%